1991
DOI: 10.3109/01913129109016260
|View full text |Cite
|
Sign up to set email alerts
|

Angiomyolipoma of the Kidney with Lymph Node Involvement

Abstract: A case of renal angiomyolipoma with regional lymph node involvement is added to 20 cases previously reported. This represents the 11th case reported in a non-tuberous sclerosis patient. The electron microscopic features of the tumor are discussed and correlated with the light microscopic findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…This puzzling lesion, probably hamartomatous in nature, arises most commonly in one or both kidneys as a solitary or multicentric mass. Extrarenal sites of AML include the liver (2, 3), spleen (4), lymph node (5,6), spermatic cord (7), penis (8), vagina (9), uterus (10), fallopian tube (11), oral cavity (12), nasal cavity (13), lung (14), heart (15), colon (16), abdominal wall (17), retroperitoneum (18), mediastinum (19,20), epidurally in the spine (21,22), subgalea aponeurotica (23), and skin (1,(24)(25)(26). To the best of our knowledge only 11 cases of cutaneous AML have been described.…”
mentioning
confidence: 99%
“…This puzzling lesion, probably hamartomatous in nature, arises most commonly in one or both kidneys as a solitary or multicentric mass. Extrarenal sites of AML include the liver (2, 3), spleen (4), lymph node (5,6), spermatic cord (7), penis (8), vagina (9), uterus (10), fallopian tube (11), oral cavity (12), nasal cavity (13), lung (14), heart (15), colon (16), abdominal wall (17), retroperitoneum (18), mediastinum (19,20), epidurally in the spine (21,22), subgalea aponeurotica (23), and skin (1,(24)(25)(26). To the best of our knowledge only 11 cases of cutaneous AML have been described.…”
mentioning
confidence: 99%
“…Furthermore, inadequate sampling of the tumour may cause the presence of adipose tissue being missed. Ansari et al [1] described areas reminiscent of LAM in regional lymph nodes of a 46-year-old woman with renal AML extending into the lymph nodes, and McIntosh et al [10] reported a case of multiple renal AML occurring with LAM of the regional lymph nodes in a 55-year-old woman. The presence of LAM-like foci in renal AML was also documented by Chan et al [3].…”
Section: Discussionmentioning
confidence: 97%
“…We searched English-language articles in the Medline database using the key words “kidney” or “renal,” “angiomyolipoma” or “hamartoma” and “lymph node.” Twenty-two papers were found. Based on the full text of the articles rather than only the abstracts, 16 papers and 25 cases were found to be relevant 419 (Table 1). Busch et al.…”
Section: Discussionmentioning
confidence: 99%
“…Twentytwo papers were found. Based on the full text of the articles rather than only the abstracts, 16 papers and 25 cases were found to be relevant [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] (Table 1). Busch et al 4 reported the first two cases of benign renal AML with regional lymph node involvement in 1976.…”
Section: Discussionmentioning
confidence: 99%